Crop Sales, Shortages and Peasant Portfolio Behaviour: An Analysis of Angola. - Azam, J; Collier, P; Cravinho, A (1994)
The article focuses on the influence of economic factors on sales of agricultural products in Angola. Between the early 1970s and the mid-1980s the volume of sales declined by around 90 percent, while during the late 1980s there was a significant recovery. This was partly due to non-economic factors such as war and drought. However, the rural economy also experienced extraordinary regulatory changes which led to a severe shortage of consumer goods. The theory of peasant supply response in a rationed economy therefore provides a starting point for the analysis and is further extended to incorporate features particular to Angola.